STUDI LITERATUR PENTINGNYA PENERAPAN PENDIDIKAN KARAKTER BAGI PENDIDIKAN FORMAL SEKOLAH MENENGAH PERTAMA - Muhammad Fiky Mayshandy (Program Studi Pendidikan IPA FKIP Universitas Jember, 2019)
Abstract Character education of junior high schools in Indonesia is arguably less preferred. In fact, it only becomes limited to discourse in formal education. This article discusses the importance of character education in formal education. Starting from looking example of applications in China. Then, the business continued its application in formal junior high school education. These efforts include the establishment of character education as one of the reasons why the important of character building for student capital to mature. Keywords: character education, design